Laminar Organization of Cerebral Cortex in Transforming Growth Factor Beta Mutant Mice (Journal of Sciences, Islamic Republic of Iran)
Transforming growth factor betas (TGF?s) are one of the most widespread and versatile cytokines. The three mammalian TGF? isoforms, ?1, ?2, and ?3, and their receptors regulate proliferation of neuronal precursors as well as survival and differentiation in neurons of developing and adult nervous system. Functions of TGF?s has a wide spectrum ranging from regulating cell proliferation and differentiation, production of extracellular matrix components, chemotaxis, and immunosuppression, to the regulation of cell death. While there is a complete lack or low levels of TGF?1 in the unlesioned nervous system, a widespread expression of TGF ?2 and TGF ?3 can be seen in different areas of the CNS and PNS. Consistent co-expression of TGF?2 and ?3 in neurons, astroglial, and Schwann cells is indicative of their multiple effects on neurons and glial cells. Based on overlapping expression of TGF ?2 and TGF ?3 and therefore their functions, our study was designed to differentiate between the functions of the two isoforms during development. Because mice lacking both isoforms die around embryonic day 15 (E15), we decided to use single homozygous and double heterozygote null mutant embryos who survive and lack any abnormal nervous system phenotype after birth. The expression pattern of markers for extracellular matrix protein such as reelin and chondroitin sulfate proteoglycan (CSPG) as well as those for cytoskeletal proteins such as microtubule associated protein (MAP), a marker for differentiated neurons, was studied in E14.5 and E16.5 mice embryos both by immunohistochemistry and in situ hybridization. Despite a reduced expression of CSPG and MAP proteins that was seen only in TGF beta 3 null mutants, Tgf?2+/+Tgf?3?/?, no abnormal localization of these markers and no change in the expression at mRNA level was noticed. The normal localization of the markers as well as their unchanged mRNA expression suggest that TGF ?2 compensates for the lack of TGF ?3 and therefore the two isoforms act in parallel to ensure the stability of brain cytoarchitecture during development.